Money and credit policies in small open less-developed economies - Shahin, Wassim Naim (1986)
he thesis addresses the issues of money and credit policies in small open less-developed economies. We examine the effects of varying monetary policy instruments on money and credit aggregates under a fixed exchange rate regime and a flexible regime when the nonborrowed base is the instrument of policy. We also analyze the effect of financing budget deficits through captive buyers of government securities on money and credit aggregates under both regimes. The thesis also deals with measures aimed at promoting and diversifying regulated markets for government securities. Studies dealing with the functioning of monetary policy in the presence of target aggregates and different monetary regimes have generally encompassed the characteristics of developed closed economies. In the last decade, several small open economies experienced major developments in their financial markets as a result of policies aimed at financial liberalization. These changes have rendered the financial environment in these countries suitable for using money and credit as instruments of stabilization. At the same time, the financial sector of these economies is still characterized by some major features salient to a less developed setting. These features include the presence of unregulated loan markets, the lack of ownership motives for holding government securities, the presence of captive buyers of these securities, and fixed deposit, loan and other major interest rates. Using a portfolio balance model that encompasses these characteristics, we reached the results that under both policy regimes, monetary authorities can vary a policy instrument and predict the direction of the move in unregulated loans. The effect of varying policy instruments on regulated loans, money supply, and the monetary base depended on the instrument itself and the regime. The same results held in the case of increasing budget deficits and changing policy instruments to promote a market for government securities. Some of our results were not in line with the analysis in the existing literature because of the differentiating characteristics of the financial markets in the study.